Editorial: Future Perspectives of Sentinel Node Mapping in Gynecological Oncology - Santoro, Angela; Inzani, Frediano; Angelico, Giuseppe; Martinelli, Fabio; Papadia, Andrea; Zannoni, Gian Franco (Frontiers in Oncology, 2022)
SLN biopsy is an intraoperative procedure for adequate staging, generally performed by a skilled multidisciplinary team. Different histopathological protocols and molecular SLN assessment have been proposed. This special issue, collecting different papers on this topic, applied to gynecological cancers, discusses the need for standardization of surgical and pathological procedures, comment the molecular aspects of SLN evaluation and the clinic benefits of this therapeutical option in daily practice.